Environmental ethics : a comparison between the views of John Locke and contemporary Māori views : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Philosophy at Massey University - Duffin, Stephen (Massey University, 1999)
The current trend, in the study of environmental ethics is to criticise the traditional Western anthropocentric attitude towards nature and by comparison praise the views of various indigenous peoples throughout the world. The Western views are labelled as a form of shallow ecology whilst those of the indigenous people are seen as much deeper. Given that there appears to be at least a prima facie difference between the two groups I will nevertheless show that there are some interesting similarities. This thesis will compare the views of one indigenous group namely, the Maori people of New Zealand with the views of John Locke who has been referred to as the great modern theorist of anthropocentrism. Using an alternative reading of Locke's texts I endeavor to show that there is a surprising coalescence of Lockean and Maori thought which indicates that we are not limited to alternative, healthier views about the environment to traditions which exist alongside the more dominant Western tradition. Instead, we find similar views in strands of the dominant tradition as well - even though these strands have not themselves been dominant.
Keywords: Locke, John, 1632-1704; New Zealand; Māori (New Zealand people); Environmental ethics